Implementasi Sistem Informasi Aplikasi Pendidikan (SIAP) terhadap Pelayanan Publik di Dinas Pendidikan dan Kebudayaan Kota Serang - Sopyan Syuri; Riswanda Riswanda; Nia Kania Kurniawati; Ipah Ema Jumiati (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2018)
A computer based service could be a measure of information-technology. The City of Serang Government adapts the principle of 'e-governance' as to measure the success of its public sector management. Educational Management Information System Apps (so-called SIAP) reflects the government efforts to come up with an up-to-date apps in terms of providing service in education. The apps nevertheless have to cope with some remaining issues come from its users. This research indicates such issues merely exist on the capacity of the apps to make it easy for users seeking data they look for when visiting either the website or when using the SIAP. The research approach is qualitative aims at measuring the web-based service quality. Cluster sampling was conducted to all population of the apps in Serang City to test out gaps between users perception and users expectation of the provided service. 'Webqual' is used as a analystical framework. The result indicates gaps within two domineering aspects namely the 'quality of information' (96,25) and the 'quality of interactions', whilst the 'functionality' aspect remains high (94.04).